The role of emotions in the perception of natural vs. play-acted dubbing: An approach to angry and sad vocal performances - Naranjo, Beatriz (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
This study examines the perception and preferences of Spanish viewers for natural vs. play-acted dubbing styles in different emotionally-loaded scenes. Two scenes portraying high-intensity emotions (anger and sadness) were selected from an American independent romantic comedy. For each scene, two different dubbed versions (natural and play-acted) were recorded. While the natural version tried to capture the paralinguistic attitudes of native conversation, the play-acted version attempted to preserve the features of dubbese with calques, formulaic routines and other vocal and paralinguistic traits identified in play-acted and dubbed speech by previous studies. In an in-situ experiment, a group of 59 viewers with the same generational profile watched the dubbed scenes and assessed whether and how both versions differed. Then, they were asked to indicate their potential preferences. Results reveal that differences in terms of naturalness between the two versions were more perceptible in the anger scene than in the sad scene. The different emotions portrayed in the scenes also seem to have played a relevant part in viewers’ preferences. Whereas participants showed a stronger preference towards natural voices in the anger scene, the play-acted version was more likable in the sad scene. The presence of visual and vocal expressions of emotion (e.g. sobbing) and background music are discussed as potential influential factors.